2010
DOI: 10.1002/chem.201002878
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design, Solid‐Phase Synthesis and Activity of Membrane‐Anchored β‐Secretase Inhibitors on Aβ Generation from Wild‐Type and Swedish‐Mutant APP

Abstract: Covalent coupling of β-secretase inhibitors to a raftophilic lipid anchor via a suitable spacer by using solid-phase peptide synthesis leads to tripartite structures displaying substantially improved inhibition of cellular secretion of the β-amyloid peptide (Aβ). Herein, we describe a series of novel tripartite structures, their full characterization by NMR spectroscopy and mass spectrometry, and the analysis of their biological activity in cell-based assays. The tripartite structure concept is applicable to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 63 publications
4
44
2
Order By: Relevance
“…That is consistent with reports showing that BACE1 inhibitor treatment of SH-SY5Y cells expressing human AβPPwt had no effect on N-terminal truncated Aβ(2-40) or Aβ(3-40) [79] and that BACE1 did not produce pGlu-Aβ(3-x) in kidney cells expressing human AβPPwt [80]. These data suggest that BACE1 inhibitors may not reduce pGlu-Aβ in most AD patients, who have wt β-secretase AβPP processing.…”
Section: Discussionsupporting
confidence: 93%
“…That is consistent with reports showing that BACE1 inhibitor treatment of SH-SY5Y cells expressing human AβPPwt had no effect on N-terminal truncated Aβ(2-40) or Aβ(3-40) [79] and that BACE1 did not produce pGlu-Aβ(3-x) in kidney cells expressing human AβPPwt [80]. These data suggest that BACE1 inhibitors may not reduce pGlu-Aβ in most AD patients, who have wt β-secretase AβPP processing.…”
Section: Discussionsupporting
confidence: 93%
“…This was supported, when using potent BACE-1 inhibitors in vitro and in vivo (Asai et al, 2006; Nishitomi et al, 2006; Hussain et al, 2007; Stanton et al, 2007; Sankaranarayanan et al, 2008). Interestingly, some studies showed that by inhibition of Aβ1-x generating β-secretase activity, alternative N-terminally truncated Aβ peptides increase (Haass et al, 1995; Schrader-Fischer and Paganetti, 1996; Takeda et al, 2004; Schieb et al, 2010; Mattsson et al, 2012). Analysis of Aβ species in BACE-1 knock-out mice likewise revealed that the generation of Aβ1-x peptides was completely abolished while N-terminally truncated Aβ variants could still be generated (Nishitomi et al, 2006).…”
Section: Conventional App Processingmentioning
confidence: 99%
“…The amyloid peptides Aβ2-40/42 cannot be assigned to BACE-1 activity and are most likely generated due to an alternative β-secretase cleaving APP between 672Asp/673Ala (Wiltfang et al, 2001; Schieb et al, 2010, 2011). Aβ2-x might act as a precursor and can likewise be processed to Aβ3-x by the alanyl-aminopeptidase activity of aminopeptidase N (Hosoda et al, 1998).…”
Section: Conventional App Processingmentioning
confidence: 99%
“…This increase was paralleled by the emergence of N-terminally truncated Aβ 5–40 in particular. Treatment of cell cultures and dogs with BACE1 inhibitors significantly reduced Aβ peptides starting at Asp-1, while amino-terminally truncated variants such as Aβ 5–40 increased [59, 83, 94]. Based on data from treatment of human neuronal and non-neuronal cells expressing wild-type APP with inhibitors of BACE and α-secretase in vitro, it has been proposed that Aβ 5–40/42 might be derived from alternative β-cleavage of APP by α-secretase-like protease(s) [94].…”
Section: Potential Enzymatic Activities Leading To N-terminal Truncatmentioning
confidence: 99%